NBN Gene Analysis and it's Impact on Breast Cancer. - Nithya, P.; ChandraSekar, A. (Journal of Medical Systems, 2019)
Single Nucleotide Polymorphism (SNP) researches have become essential in finding out the congenital relationship of structural deviations with quantitative traits, heritable diseases and physical responsiveness to different medicines. NBN is a protein coding gene (Breast Cancer); Nibrin is used to fix and rebuild the body from damages caused because of strand breaks (both singular and double) associated with protein nibrin. NBN gene was retrieved from dbSNP/NCBI database and investigated using computational SNP analysis tools. The encrypted region in SNPs (exonal SNPs) were analyzed using software tools, SIFT, Provean, Polyphen, INPS, SNAP and Phd-SNP. The 3'ends of SNPs in un-translated region were also investigated to determine the impact of binding. The association of NBN gene polymorphism leads to several diseases was studied. Four SNPs were predicted to be highly damaged in coding regions which are responsible for the diseases such as, Aplastic Anemia, Nijmegan breakage syndrome, Microsephaly normal intelligence, immune deficiency and hereditary cancer predisposing syndrome (clivar). The present study will be helpful in finding the suitable drugs in future for various diseases especially for breast cancer.